Biosynthesis of membrane-derived oligosaccharides: a periplasmic phosphoglyceroltransferase. - Goldberg, D E (1981)
Membrane-derived oligosaccharides (MDO) are glucose-containing constituents of the periplasmic space of Escherichia coli whose biosynthesis is closely linked to the metabolism of membrane phospholipids. A periplasmic enzyme has now been discovered that catalyzes the transfer of phosphoglycerol residues between species of MDO or to certain glucose-containing model substrates such as gentiobiose (6-O-beta-D-glucopyranosyl-D-glucose). The partially purified enzyme has an apparent molecular weight of about 56,000 in gel permeation chromatography, and has an absolute requirement for divalent cations, of which Mn2+ is most active. Although the transferase activity appears to be the physiological function of the enzyme, at low concentrations of acceptor, the enzyme (Enz) acts as a cyclase, with the liberation of cyclic 1(3),2-phosphoglycerol, suggesting the following mechanism: (formula, see text).